1994
DOI: 10.1002/qua.560520853
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic density-functional studies of naked and ligated gold clusters

Abstract: Electronic structure investigations on a broad range of gold compounds, including naked and ligated gold clusters, are reviewed. The calculations have been carried out with a recently introduced relativistic variant of the linear combination of Gaussian-type orbitals density-functional (LCGTO-DF) method which affords all-electron investigations for very large systems. The accuracy of the method will be evaluated for the gold dirner. Then the electronic structure of the naked cluster AuSS is studied, both in Ih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 49 publications
9
97
0
Order By: Relevance
“…ECP ‫ס‬ effective core potential; DFT ‫ס‬ density functional theory. tion calculations at both the singles ‫ם‬ doubles level [28] and also with triplet energy corrections [8], the LCGTO-DF method described earlier [8] and a coupled electron pair approximation (CEPA) calculation using a pseudopotential [33]. With the exception of the LCGTO-DF results, all of these cited calculations underestimate the IP.…”
Section: Atomic Propertiesmentioning
confidence: 94%
See 2 more Smart Citations
“…ECP ‫ס‬ effective core potential; DFT ‫ס‬ density functional theory. tion calculations at both the singles ‫ם‬ doubles level [28] and also with triplet energy corrections [8], the LCGTO-DF method described earlier [8] and a coupled electron pair approximation (CEPA) calculation using a pseudopotential [33]. With the exception of the LCGTO-DF results, all of these cited calculations underestimate the IP.…”
Section: Atomic Propertiesmentioning
confidence: 94%
“…Our results provide good agreement in comparison to the experimental properties. The only previous study has been that of Rö sch et al [8] and Hä berlen and Rö sch [9], using the LGGTO-DF method and a large basis set. The authors report a Au-C bondlength of 2.00Å and a Au-P bondlength of 2.29Å , nearly identical to the experimental values.…”
Section: Organogold Moleculesmentioning
confidence: 98%
See 1 more Smart Citation
“…The small clusters with fewer than 20 atoms were thoroughly investigated by several research groups [29,30]. Some of the earliest work on large systems focused on symmetrical structures.…”
Section: Gold Clustersmentioning
confidence: 99%
“…Some of the earliest work on large systems focused on symmetrical structures. Haberlen et al [29] examined octahedral and icosahedral Au 55 using the Vosko, Wilks and Nusair (VWN) functional and found that the Kohn-Sham orbitals and their energy orderings agreed well with a jellium model once energy level splittings due to symmetry reduction were considered.…”
Section: Gold Clustersmentioning
confidence: 99%